A set-covering formulation for a drayage problem with single and double container loads - A. Ghezelsoflu; M. Di Francesco; A. Frangion; P. Zuddas (Journal of Industrial Engineering International, 2018)
This paper addresses a drayage problem, which is motivated by the case study of a real carrier. Its trucks carry one or two containers from a port to importers and from exporters to the port. Since up to four customers can be served in each route, we propose a set-covering formulation for this problem where all possible routes are enumerated. This model can be efficiently solved to optimality by a commercial solver, significantly outperforming a previously proposed node-arc formulation. Moreover, the model can be effectively used to evaluate a new distribution policy, which results in an enlarged set of feasible routes and can increase savings w.r.t. the policy currently employed by the carrier.
Keywords: 650; Drayage; Vehicle routing problem; Street-turns; Set covering